Quantity and quality limit detritivore growth: mechanisms revealed by ecological stoichiometry and co‐limitation theory. Issue 12 (18th October 2017) - Halvorson, Halvor M.; Sperfeld, Erik; Evans‐White, Michelle A.
Abstract: Resource quantity and quality are fundamental bottom‐up constraints on consumers. Best understood in autotroph‐based systems, co‐occurrence of these constraints may be common but remains poorly studied in detrital‐based systems. Here, we used a laboratory growth experiment to test limitation of the detritivorous caddisfly larvae Pycnopsyche lepida across a concurrent gradient of oak litter quantity (food supply) and quality (phosphorus : carbon [P:C ratios]). Growth increased simultaneously with quantity and quality, indicating co‐limitation across the resource gradients. We merged approaches of ecological stoichiometry and co‐limitation theory, showing how co‐limitation reflected shifts in C and P acquisition throughout homeostatic regulation. Increased growth was best explained by elevated consumption rates and improved P assimilation, which both increased with elevated quantity and quality. Notably, C assimilation efficiencies remained unchanged and achieved maximum 18% at low quantity despite pronounced C limitation. Detrital C recalcitrance and substantive post‐assimilatory C losses probably set a minimum quantity threshold to achieve positive C balance. Above this threshold, greater quality enhanced larval growth probably by improving P assimilation toward P‐intensive growth. We suggest this interplay of C and P acquisition contributes to detritivore co‐limitation, highlighting quantity and quality as potential simultaneous bottom‐up controls in detrital‐based ecosystems, including under anthropogenic change like nutrient enrichment.